(untitled) (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1979-81) Chief Editor - GoPAL SWARUP, Nematology Divn., I. A. R. I., New Delhi Editor - D. R. DAs GUPTA, Nematology Divn., I. A. R. I., New Delhi Members - C. L. SETHI, Nematology Divn., I. A. R. I., New Delhi - K. C. SANWAL, N. B. P. G. R., New Delhi - ABRAR M. KHAN, Botany Dept., A. M. U., Aligarh - S. KHZRA, Zoology Dept., Meerut University, Meerut - T. S. MUTHUKKISHNAN, Biology Dept., T. N. A. U., Coimbatore -M. S.JAIRAPURI, Zoology Dept., A. M. D., Aligarh